The Effect of Integrated Marketing Communication on the Level of Tourist Visits in Bosowa Indah Beach Tourism - Ilma Wulansari Hasdiansa; Sitti Hasbiah (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2023)
This study aims to determine whether the dimensions of integrated marketing communications, namely Advertising, Direct Marketing, Sales Promotion, Personal Selling and Public Relations have an influence on the level of tourist visits to Bosowa Indah Beach Tourism. The population in this study were visitors to Bosowa Indah Beach Tourism. Samples were taken as many as 100 respondents using the Non-Probability Sampling technique with a Purposive Sampling approach. Based on the research results, the indicators in this study are valid and the variables are reliable. In testing the classical assumptions, the multicollinearity-free regression model, heteroscedasticity does not occur, and is normally distributed. The individual order of each variable that has the most influence is Sales Promotion variable with a regression coefficient of 0.281, then Direct Marketing with a regression coefficient of 0.131, then followed by Personal Selling with a regression coefficient of 0.016, and Advertising with a regression coefficient of -0.035 while the variable that has a negative effect is Public Relations with a regression coefficient of -0.064.